Real-time information extraction of an electric vehicle - Ferreira, João C. (2012)
In this paper is presented the development of a project to extract, in real-time, information’s related with an Electric Vehicle (EV). This project was elaborated to extract data from an EV battery charging device developed at the University of Minho, and from an EV prototype, the VEECO (Veículo Eléctrico ECOlógico – Ecologic Electric Vehicle), developed in a cooperation project of ISEL (Lisbon Superior Institute of Engineering) and the Portuguese company VE. The main goal of this project consists in collecting and transmitting the extracted data to inform the EV driver about the performance and the real behavior of the EV. Thereby, it is created an open interface to manage, in real-time, the main data related with the EV, as the batteries SoC (State-of-Charge), the EV speed, and internal temperatures (like the temperatures of the batteries, motor and power electronics inverter), as well as to control the start and stop of the batteries charging process, and to optimize the charging program (to define the best algorithm to preserve the batteries lifespan). This interface also controls the discharging process of the batteries, in order to make possible to deliver back to the electrical power grid part of the stored energy in the batteries, which is defined by the concept Vehicle-to-Grid (V2G). In the paper are presented and described the two main parts of this work: the real-time information extraction system and the charging device.